2023
DOI: 10.1002/eqe.3846
|View full text |Cite
|
Sign up to set email alerts
|

Seismic damage evaluation of unanchored nonstructural components under combined effects of horizontal and vertical near‐fault ground motions

Abstract: With consideration of seismic resilience, damage of nonstructural components (NSCs) attracts significant attentions. Most previous studies focused on dynamic behaviors of NSCs under horizontal excitations. Near‐fault earthquakes, however, have strong vertical ground motion components, but few studies assessed their influence on seismic damage of NSCs. In this study, the seismic responses of unanchored NSCs under near‐fault earthquakes with strong vertical components are investigated. Response history analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…To the best of the authors' knowledge, there is no solid agreement on the effect of vertical ground motions on seismic responses of NSCs. Wang et al 22 identified that the slender freestanding NSCs are more vulnerable to the presence of vertical ground motions. For such NSCs or similar cases, the surrogate models for estimating the combined effects of triaxial excitations should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To the best of the authors' knowledge, there is no solid agreement on the effect of vertical ground motions on seismic responses of NSCs. Wang et al 22 identified that the slender freestanding NSCs are more vulnerable to the presence of vertical ground motions. For such NSCs or similar cases, the surrogate models for estimating the combined effects of triaxial excitations should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the authors’ knowledge, there is no solid agreement on the effect of vertical ground motions on seismic responses of NSCs. Wang et al 22 . identified that the slender freestanding NSCs are more vulnerable to the presence of vertical ground motions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations